2010
DOI: 10.1007/s12544-010-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to assess pedestrian crossing safety

Abstract: Purpose: The safety level of a pedestrian crossing is affected by infrastructure characteristics and vehicular and pedestrian traffic level. This paper presents a methodology that allows assessing the safety level of a pedestrian crossing, regulated or not by traffic light, in an urban area according to the features of the crossing. Methods: A hierarchical structure representing factors influencing crossing safety has been developed and the relative contributions of each factor were calculated using AHP method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
0
23
0
5
Order By: Relevance
“…In fact, people in the urban area would like to make on foot, and then to adapt the road system to create a network of safe and attractive routes for them (Basile et al [25]; Dommes et al [26]; Saidul Islam et al [27]). …”
Section: The Road Accidents Involving Urban Goods Vehicles and Pedestmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, people in the urban area would like to make on foot, and then to adapt the road system to create a network of safe and attractive routes for them (Basile et al [25]; Dommes et al [26]; Saidul Islam et al [27]). …”
Section: The Road Accidents Involving Urban Goods Vehicles and Pedestmentioning
confidence: 99%
“…An application of such an index is provided by Basile et al [25], which index was used for evaluating and ranking more than 200 junctions in 17 European cities.…”
Section: The Road Accidents Involving Urban Goods Vehicles and Pedestmentioning
confidence: 99%
“…Sisiopiku and Akin [21] studied the pedestrian perceptions of various signalised and un-signalised intersections and suggested that the distance of the crosswalk to the desired destinations is the most influential factor in making a decision to cross. Basile et al [22] used the AHP method to assess the safety level of pedestrians at regulated and not regulated crossings: a composite indicator for crossing safety, together with some other specific indicators included in the assessment allowed to rank the crossings on the basis of their spatial characteristics and to suggest the priority of interventions by highlighting the issues that need to be addressed. The absence of pedestrian refuge islands, improper traffic light timing, on-street car parking obstructing the visibility, and accessibility problems due to obstacles along the pedestrian crossing, emerged as the most influential factors for pedestrian safety.…”
Section: Intersections In Walkability Studies: State Of the Artmentioning
confidence: 99%
“…Pedestrian level of service measures and assessments (PLOS) represent the field of studies that deals more deeply with the factors of the built environment responsible of the hindering effect of road intersections on pedestrian accessibility. PLOS introduced by Fruin [11] and later internalized by TRB's HCM [12] is a measure of the operational quality of pedestrian facilities based on finegrained analysis of physical space and traffic flows. Researchers broadly employed this method for enrich the set of factors affecting pedestrian behavior both along sidewalks and at crossings.…”
Section: Incorporation Of the Qualities Of Road Intersections In Walkmentioning
confidence: 99%